ALIH WAHANA NOVEL MERINDU CAHAYA DE AMSTEL KARYA ARUMI EKOWATI MENJADI FILM - Ratna Dwi Anjani Putri; Ida Ayu Made Wedasuwari; I Nyoman Adi Susrawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research is a qualitative descriptive study that aims to describe the shape of the plot, setting, and characters in the novel and film Merindu Cahaya de Amstel by Arumi Ekowati. This data collection was carried out using the method of observation, reading, listening, and taking notes. The data obtained were analyzed by descriptive qualitative. The steps in analyzing the data are by classifying, presenting the data, and drawing conclusions. The research results obtained were in the form of turning the novel into a film in the form of shrinking, adding, and varying changes in plot, setting, and characters in the novel and film Merindu Cahaya de Amstel by Arumi Ekowati. The transformation of the novel into a film in the form of shrinking, adding, and varying changes in the plot, setting, and characters was done because the film had limited time or duration so that it could not include the whole story in the novel.